Supervisors' experience of delivering individual clinical supervision to qualified therapists: a meta-ethnographic synthesis. Issue 1 (3rd May 2019) - Forshaw, Gemma; Sabin-Farrell, Rachel; Schröder, Thomas
Abstract : Purpose: The purpose of this paper is to systematically identify, appraise and synthesise qualitative literature exploring the experience, both positive and negative, of clinical supervision from the supervisor's perspective. Design/methodology/approach: A systematic search of three databases, grey literature, reference lists and citations was conducted. Six articles met the inclusion criteria and their quality was critically appraised by using a modified version of the Critical Appraisal Skills Programme tool. Data extracted from the articles were synthesised using meta-ethnography. Findings: Four key themes were identified: experiencing difficulties in clinical supervision, responsibility, similarities to therapy and capabilities as a supervisor. These demonstrated that the role of a supervisor has the potential to be both beneficial and harmful to personal and professional development. Research limitations/implications: The quality of the studies was variable. Further research is required to explore how supervisors manage difficult experiences to ensure personal development and growth. Practical implications: Clinical implications include the need for employers to consider the additional pressure associated with providing clinical supervision and to ensure that appropriate support is available. Results complement previous research on the bi-directionality of parallel process in clinical supervision. Originality/value: This review presents an original synthesis of the supervisor's experience of delivering clinical supervision to qualified therapists. This is achieved by utilising a systematic methodology and appraising the quality of the studies included. The review highlights how the effects of clinical supervision are not limited to the supervisee, but also experienced by the supervisor. The competing demands and responsibilities associated with clinical supervision impact upon the supervisor's experience, both positively and negatively. When beneficial, delivering clinical supervision can lead to personal and professional growth in addition to the acquisition of new skills.